(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Damage to liver function is the most common cause of patients or doctors stopping treatment. Anti tuberculosis (OAT) drug-induced hepatotoxicity is mainly caused by oxidative stress caused by drugs and metabolites. Subchronic toxicity is one of the conditions for testing long-term used drugs such as OAT. The research aims to determine the potential of miana leaf extract (EDM) as a hepatoprotector and prevent toxicity due to OAT administration. The study used 5 groups of Wistar rat test animals namely K1 (normal mice given placebo); K2 (OAT-induced mice given placebo); K3 (OAT-induced mice given Makassar EDM); K4 (OAT-induced mice given EDM Kupang); K5 (OAT-induced mice given Silymarin). Tests on mice were carried out after 30 days of treatment with parameters SGOT, SGPT, total bilirubin, creatinine and liver histopathology. The results showed that EDM has the potential as a hepatoprotector by preventing an increase in SGOT, SGPT and total bilirubin so as to avoid liver damage due to OAT induction. EDM has the potential to prevent toxicity due to the administration of OAT with creatinine parameters.